Program “Kampung Emas” Sebagai Upaya Percepatan Penurunan Angka Stunting di Kelurahan Embong Kaliasin, Surabaya - Andriani, Dinda; Irwanto, Bian Shabri Putri (Universitas Nusantara PGRI Kediri, 2024)
The reduction in stunting rates must be more comprehensive in overcoming it, because this case is one of the national priorities in terms of human resource development. So that in handling stunting cases in Surabaya using the